Distribution and relative age of endemism across islands worldwide - Veron, Simon (Sci Rep, 2019)
Islands have remarkable levels of endemism and contribute greatly to global biodiversity. Establishing the age of island endemics is important to gain insights into the processes that have shaped the biodiversity patterns of island biota. We investigated the relative age of monocots across islands worldwide, using different measures of phylogenetic endemism tested against null models. We compiled a species occurrence dataset across 4,306 islands, and identified 142 sites with neo-, paleo-, mixed and super-endemism. These sites were distributed across the world, although they tended to be more common at low latitudes. The most frequent types of endemism were mixed and super-endemism, which suggests that present-day island biodiversity has frequently been shaped by processes that took place at different points in times. We also identified the environmental factors that contributed most to different types of endemism; we found that latitude, habitat availability and climate stability had a significant impact on the persistence of ancient taxa and on recent diversification events. The islands identified here are irreplaceable both for the uniqueness and the evolutionary history of their flora, and because they are a source of “option values” and evolutionary potential. Therefore, our findings will help guide biodiversity conservation on a global scale.